Peran Sentral Guru dalam Pendidikan Karakter di Era Digital - Hazyimara, Karunia; Wenty Septria Darma Suwarni (SETYAKI : Jurnal Studi Keagamaan Islam, 2023)
Moral degradation is increasingly coming to the surface, this is one of the negative impacts of the progress of the times that have entered the digital era. The progress of the times can actually be an opportunity to increase competitiveness, because it’s easy to access all sources of knowledge. But the facts, on the ground show that the progress of the times also has a negative effect, the one is moral degradation. This happens because students don’t have the maturity of thinking and need strict instructions in its use. Character as a personality formed from habits can be a fortress for students to face the increasingly brilliant progress of the times. Character cultivation cannot be separated from the role of teachers as educators in schools who have obligations in shaping the character of students. This study will discuss the position of teachers in building the character of students so that students have mental maturity to face existing changes. This research uses a type of literature research with a qualitative approach. To support the use of these types and approaches, researchers collect data using documentation methods. The results of this study show that character education is an important guide for students to face changes in the progress of the times. Through noble character, students can sort out what is appropriate and what is not. It takes a massive role of teachers so that character cultivation in students is maximized. This character education does not only focus on one level of learning but must be taught throughout life.